Vitamin D deficiency in children - Ashraf, Mohd; Ishaq, Mohammad; Parrey, Nazir Ahmed; Ahmed, Kaisar (Asian Journal of Medical Sciences, 2014)
Background: Vitamin D deficiency in children is an important medical entity commonly diagnosed during early childhood. Prevalence and incidence of vitamin D deficiency in children is underestimated and can have far reaching consequences as per the latest evidence. Children at high risk should be identified and treated accordingly to avoid the treatable misadventures of future life. Aim: The purpose of this review is to provide summary of the latest research in particular to the practical aspects of vitamin D deficiency in children. Methods: A literature search in PubMed, Medline, Embase, Scopus, Google Scholar, and DOAJ was conducted, regarding pediatric vitamin D deficiency related research and review articles in English language, using keywords or phrases such as bones; childhood allergy; calcium; children; diabetes mellitus type 1; respiratory infections; rickets; failure to thrive, 25-OH vitamin D. Conclusion: Despite major advances in unfolding the classical and non-classical role of vitamin D in various health related events in children, yet most of the pediatric population is vitamin D deficient even in countries like India with ample sunlight. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10199 Asian Journal of Medical Sciences Vol.6(1) 2015 1-7